Recombination between gtfB and gtfC Is Required for Survival of a dTDP-Rhamnose Synthesis-Deficient Mutant of Streptococcus mutans in the Presence of Sucrose - Yamashita, Yoshihisa (American Society for Microbiology, 1999)
The rml genes are involved in dTDP-rhamnose synthesis in Streptococcus mutans. A gene fusion between gtfB and gtfC, which both encode extracellular water-insoluble glucan-synthesizing enzymes, accompanied by inactivation of the rml genes was observed for cells grown in the presence of sucrose. The survival rates of rml mutants isolated in the absence of sucrose were drastically reduced in the presence of sucrose. The rates were consistent with the frequency of spontaneous gene fusions between gtfB and gtfC, suggesting that the spontaneous recombinant organisms were selected in the presence of sucrose. The rml mutants with a gtfB-gtfC fusion gene had markedly reduced water-insoluble glucan synthetic activity and lost the ability to colonize glass surfaces in the presence of sucrose. These results suggest that the rml mutants of S. mutans, which are defective in dTDP-rhamnose synthesis, can survive only in the absence of water-insoluble glucan synthesis.